Stability study of slope reinforced with piles under steady unsaturated flow conditions. (May 2019) - Yang, Minghui; Deng, Bo
Abstract: In this study, based on the log-spiral upper bound limit analysis method that integrated with the generalized effective stress, a new formula for calculating the lateral stabilizing force provided by a row of piles required to increase the slope safety factor to a desired value under vertical steady unsaturated flow was developed, and the most critical solutions were obtained by the optimization method. Moreover, the proposed method can be simplified to the case without piles for computing the stability number for a slope in the limit state of failure. By comparing the results of the proposed method to others for some examples, its feasibility was verified. Numerical study for the parametric effects was presented, indicating that limit lateral stabilizing force depends strongly on the soil types, the slope geometry, the seepage conditions and that in routine design without consideration of suction stress can lead to a less conservative result in clay and sand, but can obtain a relatively safe result in silt and loess. This paper gives some useful suggestions for engineering application and provides a useful method for further study.